Association between rs2275913 single‐nucleotide polymorphism of the interleukin‐17A gene and perioperative analgesic use in cosmetic orthognathic surgery - Seii Ohka; Daisuke Nishizawa; Junko Hasegawa; Kaori Takahashi; Kyoko Nakayama; Yuko Ebata; Ken‐ichi Fukuda; Kazutaka Ikeda (Wiley, 2018)
Abstract Aim Interleukin‐17A (IL‐17A) plays an essential role in tissue inflammation by inducing proinflammatory cytokine and chemokine production and is related to innate immune reactions. IL‐17A also contributes to neuroinflammation, neuropathic pain, and mechanical hypersensitivity after peripheral nerve injury in rodents. To clarify the contribution of IL‐17A to pain‐related phenotypes in humans, we investigated the association between pain‐related phenotypes and the rs2275913 single‐nucleotide polymorphism (SNP) of the IL‐17A gene, which has been reported to be associated with rheumatoid arthritis, ulcerative colitis, and some cancers. Methods The present study used a correlational design to examine the impact of the rs2275913 SNP on postoperative pain‐related phenotypes in a group of patients who underwent cosmetic orthognathic surgery. Results Carriers of the AA genotype had higher opioid requirements during and after surgery than carriers of the AG and GG genotypes (P = .009). Linear regression analysis indicated that opioid requirements linearly increased as the copy number of the A allele of the SNP increased (P = .008). Conclusions Opioid requirements during and after surgery are enhanced in carriers of the AA genotype of the rs2275913 SNP of the IL‐17A gene, possibly through an enhancement of IL‐17A function that induces inflammation that is related to the inflammatory pain stimulus.